Mechanochemically triggered topology changes in expanded porphyrins - Bettens, Tom; Hoffmann, Marvin; Alonso, Mercedes; Geerlings, Paul; Dreuw, Andreas; Proft, Frank De (Chemistry - a European journal, 2021)
A hitherto unexplored class of molecules for molecular force probe applications are expanded porphyrins. This work proves that mechanical force is an effective stimulus to trigger the interconversion between Hückel and Möbius topologies in [28]hexaphyrin, making these expanded porphyrins suitable to act as conformational mechanophores operating at mild (sub-1 nN) force conditions. A straightforward approach based on distance matrices is proposed for the selection of pulling scenarios that promote either the planar Hückel topology or the three lowest lying Möbius topologies. This approach is supported by quantum mechanochemical calculations. Force distribution analyses reveal that [28]hexaphyrin selectively allocates the external mechanical energy to molecular regions that trigger Hückel-Möbius interconversions, explaining why certain pulling scenarios favor the Hückel two-sided topology and others favor Möbius single-sided topologies. The meso-substitution pattern on [28]hexaphyrin determines whether the energy difference between the different topologies can be overcome by mechanical activation.